Exenatide improves hepatocyte insulin resistance induced by different regional adipose tissue - Bai, Chuanmin; Wang, Yujun; Niu, Zhi; Guan, Yaxin; Huang, Jingshan; Nian, Xin; Zuo, Fan; Zhao, Juan; Kazumi, Tsutomu; Wu, Bin (Frontiers in Endocrinology, 2022)
Obesity is resulted from energy surplus and is characterized by abnormal adipose tissue accumulation and/or distribution. Adipokines secreted by different regional adipose tissue can induce changes in key proteins of the insulin signaling pathway in hepatocytes and result in impaired hepatic glucose metabolism. This study aimed to investigate whether exenatide affects key proteins of IRS2/PI3K/Akt2 signaling pathway in hepatocytes altered by the different regional fat depots. Six non-obese patients without endocrine diseases were selected as the research subjects. Their subcutaneous adipose tissue (SAT) and visceral adipose tissue (VAT)were co-cultured with HepG2 cells in the transwell chamber. In the presence or absence of exenatide, adipokines content in the supernatant of each experimental group was detected by ELISA. In addition, HepG2 cells in each co-culture group with and without insulin were collected, and the expression of key proteins IRS2, p-IRS2(S731), PI3K-p85, Akt2, and p-Akt2(S473) was detected by western blotting (WB). The results showed that the adipokines IL-8, MCP-1, VEGF, and sTNFR2 in the supernatant of HepG2 cells induced by different regional adipose tissue were significantly higher than those in the HepG2 group, and VAT released more adipokines than SAT. Furthermore, these adipokines were significantly inhibited by exenatide. Importantly, the different regional fat depot affects the IRS2/PI3K/Akt2 insulin signaling pathway of hepatocytes. Exenatide can up-regulate the expression of hepatocyte proteins IRS2, PI3K-p85, p-Akt2(S731) inhibited by adipose tissue, and down-regulate the expression of hepatocyte proteins p-IRS2(S731) promoted by adipose tissue. The effect of VAT on the expression of these key proteins in hepatocytes is more significant than that of SAT. But there was no statistical difference in the expression of Akt2 protein among each experimental group, suggesting that exenatide has no influence on the expression of Akt2 protein in hepatocytes. In conclusion, exenatide may improve hepatic insulin resistance (IR) by inhibiting adipokines and regulating the expression of key proteins in the IRS2/PI3K/Akt2 pathway.